I.vi.2. Miscellaneous letters and draft letters by John Pitt Kennedy - Kennedy, John Pitt, 1796-1879; Board of Public Works (1853)
Includes a draft letter to the military secretary of the Commander in Chief , waiving his appearance before a board of examination and listing his service to date (1853); two letters from Frederick Robinson, of a spiritual nature ; a letter from the Board of Public Works (St. Giles District)signed by the chairman, James Ashmore; and an incomplete draft to an unknown recipient.
Keywords: Kennedy, John Pitt, -- 1796-1879; Board of Public Works; Politics and government; Spiritual direction -- Christianity